Burnout in emergency department healthcare professionals is associated with coping style: a cross-sectional survey. Issue 9 (20th January 2015) - Howlett, M; Doody, K; Murray, J; LeBlanc-Duchin, D; Fraser, J; Atkinson, PR
Abstract : Introduction: Ineffective coping may lead to impaired job performance and burnout, with adverse consequences to staff well-being and patient outcomes. We examined the relationship between coping styles and burnout in emergency physicians, nurses and support staff at seven small, medium and large emergency departments (ED) in a Canadian health region (population 500 000). Methods: Linear regression with the Coping Inventory for Stressful Situations (CISS) and Maslach Burnout Inventory (MBI) was used to evaluate the effect of coping style on levels of burnout in a cross-sectional survey of 616 ED staff members. CISS measures coping style in three categories: task-oriented, emotion-oriented and avoidance-oriented coping; MBI, in use for 30 years, assesses the level of burnout in healthcare workers. Results: Task-oriented coping was associated with decreased risk of burnout, while emotion-oriented coping was associated with increased risk of burnout. Discussion: Specific coping styles are associated with varied risk of burnout in ED staff across several different types of hospitals in a regional network. Coping style intervention may reduce burnout, while leading to improvement in staff well-being and patient outcomes. Further studies should focus on building and sustaining task-oriented coping, along with alternatives to emotion-oriented coping.